Quantitation of Phenolic Compounds Related to Antioxidant and Antiosteoporosis Activities in Ripe and Unripe Maesil (Prunus mume) - Chong Woon Cho; Young Sik Park; Xi-Tao Yan; Hyun June Kim; Young Ho Kim; Kyung Tae Kim; Chu Van Men; Jong Seong Kang (Journal of Food Quality)
The fruits of Prunus mume, maesil (Rosaceae), have been widely used as a valuable source of foods and herbal medicines from ancient times in Northeast Asia. Specially, phenolic compounds of main compounds in maesil were reported to have various activities. This study aims to develop the simultaneous analytical method of nine phenolic compounds in maesil and to evaluate these compound contents in samples during the ripeness. Twenty-one species of samples and nine phenolic compounds were used for this study. In results, compounds 1–9 contents in unripe fruits were 0.16∼1.81 mg/g. However, these compounds in ripe samples were 0.09∼1.66 mg/g. Compounds 1–9 contents in ripe fruits were generally reduced rather than those in unripe fruits. Otherwise, the contents of compounds 2, 5, 8, and 9 in seed part were relatively higher than those in flesh part. In contrast, contents of compounds 1, 3, and 7 in flesh part were relatively higher than those in seed part. Generally, the contents of compounds 1–9 in unripe fruits were higher than those in ripe fruits. However, the contents of compounds 1–9 in each part (seed and fresh) of fruits were different according to species of compounds. It indicates that the selection of harvesting time and process part of fruits as the source of foods and medicines is important.